The Effectiveness of Thematic Learning with Thinking Actively in a Social Context and Creative Problem Solving Learning Models on Divergent Thinking Skills - Fauziah, Muna; Marmoah, Sri; Murwaningsih, Tri (International Journal for Educational and Vocational Studies, 2020)
The aim of this research is to find out the effect of Thinking Actively in a Social Context, Creative Problem Solving, and Direct Instruction learning models on students' divergent thinking skills. The quantitative research with a quasi-experimental method was used as the research approach. The research subjects include the fifth-grade students at the public elementary schools in Laweyan District, Surakarta, Indonesia. The data were collected using test and non-test techniques. They were then analyzed using the prerequisite test, hypothesis test and multiple-comparison test. The results show that the learning model has an effect on divergent thinking skills. The selection of TASC and CPS learning models has an effect on the students activeness in learning, so teachers can consider these models to be applied in learning with integrated thematic teaching materials in the 2013 curriculum.